Actividad fibrinolitica en venenos de serpientes peruanas de los géneros bothrops, lachesis y crotalus - Collantes, Hugo G.; Zavaleta Martínez-Vargas, Alfonso; Salas, Maria (Pontificia Universidad Católica del Perú, 1992)
We studied the presence of fibrinolytic activity in five dried peruvian snake venoms using fibrin clots formed by one partially purified fraction of Thrombin-like enzyme from L. muta muta. In all venoms studied, fibrinolysis were detected in absence of plasmin in the range from 16,3 to 57,5 U/h mgprotein. This results demonstrate the existence of proteolytic enzymes in Peruvian Viperid snake venoms that act upon fibrin. The L. muta muta venom showed the higher activity (57 ,5), followed in down order by B. barnetti (45,2) B. pictus (29,4), C. durisus terrificus (22,5) and B. brazilü venom (16,3).

Se estudia la presencia de actividad fibrinolítica en los venenos de cinco serpientes peruanas empleando coágulos de fibrina formados a partir de fibrinógeno bovino y una enzima semejante a trombina de L. muta muta parcialmente purificada Los cinco venenos estudiados presentaron actividad fibrinolítica en ausencia de plasmina (rango: 16,3 a 57,5 U/h mg protefua), lo que demuestra la existencia de enzimas proteolíticas en los venenos de vipéridos peruanos, que actúan directamente sobre la fibrina. El veneno de L. muta muta presentó la mayor actividad enzimática específica (57 ,5), seguido en orden decreciente por B. barnetti (45,2),B.pictus (29,4), C. durisus terrificus (22,5) y B. brazilü (16,3).
Keywords: Snake Venom; Fibrinolytic Activity; Coagulant; Thrombinlike; Química; Venenos de Serpiente; Fibrinólisis; Coagulación; https://purl.org/pe-repo/ocde/ford#1.04.00